2021
DOI: 10.3390/ma14226897
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Aviation Polymer Composites at Various Weight Fractions of Physical Modifier

Abstract: The aim of this study was to determine the effect of a selected physical modifier with different granularity and mass percentage on the dynamics of aerospace polymer composites. The tests were carried out on samples made of certified aerospace materials used, among other purposes, for the manufacture of aircraft skin components. The hybrid composites were prepared from L285 resin, H286 hardener, GG 280T carbon fabric in twill 2/2 and alumina (Al2O3, designated as EA in this work). The manufactured composites c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, the increased use of composite materials is caused by the possibility of changing their structural properties by adding modifiers to their composition. These modifiers and reinforcing fibers improve the material properties such as density, hardness, impact strength, mechanical and tribological properties, and reduced flammability [13][14][15][16][17]. The results of the research described in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increased use of composite materials is caused by the possibility of changing their structural properties by adding modifiers to their composition. These modifiers and reinforcing fibers improve the material properties such as density, hardness, impact strength, mechanical and tribological properties, and reduced flammability [13][14][15][16][17]. The results of the research described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the mass share of the physical modifier resulted in the increase of the material's compliance. In another study [15], research was carried out to determine the effect of a selected physical modifier with different granularity and the mass percentage that was a component of the tested material on the vibration behavior of composite beams in the frequency range covering the first three forms of vibration. The authors showed that the dynamics of composite beams varied with the proportion of modifier.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers around the world have taken steps to improve the operational properties of this group of materials by using various types of reinforcements, e.g., fibers [8][9][10][11]. A reinforcement forms a composite that is more attractive than pure plastic due to its low density, greater strength, stiffness, and increased abrasion resistance [12][13][14][15][16]. The newly developed materials and their possible degradation products must also be non-toxic to normal cells in the human body [17][18][19].…”
Section: Introductionmentioning
confidence: 99%